Fetal brain extraction from magnetic resonance image (MRI) of human fetus. (3rd April 2018) - Somasundaram, K.; Gayathri, S. P.; Rajeswaran, R.; Manjiri, Dighe
ABSTRACT: Study of a fetus is a rapidly growing field of research and it requires fetal brain segmentation. Automatic segmentation of the fetal brain from magnetic resonance imaging (MRI) is challenging, due to the highly variable size and shape of the developing brain, possible brain structure abnormalities, movement of the fetus and a poor resolution of fetal MRI scans. This is in contrast to adult brain segmentation, where the brain structure is stable and several established methods exist. This paper presents a fully automatic segmentation method to segment the fetal brain portion from MRI. The segmentation pipeline developed in this study includes contrast enhancement, region growing and hole filling. Twenty-five volumes of retrospective fetal MRI are used in this work. Experimental results show that this method can successfully segment the fetal brain from magnetic resonance images which are comparable to that of a semi-automatic method.